Spying through a Glass Darkly : American Espionage against the Soviet Union, 1945 - 1946 - Alvarez, David J. (Book collections on Project MUSE., 2016)
"This book chronicles the struggles of American intelligence agencies to come to grips with Europe's new postwar realities, including the growing dominance of the Soviet Union, its recent ally in the war against Hitler's Germany. Focusing on the Strategic Services Unit, which rose from the ashes of the OSS and took on missions that would eventually be embraced by the CIA, Alvarez illuminates a long-neglected and poorly understood chapter in what became the Cold War"--Provided by publisher.